2017
DOI: 10.1016/j.ejphar.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

CO-independent modification of K + channels by tricarbonyldichlororuthenium(II) dimer (CORM-2)

Abstract: Although toxic when inhaled in high concentrations, the gas carbon monoxide (CO) is endogenously produced in mammals, and various beneficial effects are reported. For potential medicinal applications and studying the molecular processes underlying the pharmacological action of CO, so-called CO-releasing molecules (CORMs), such as tricabonyldichlororuthenium(II) dimer (CORM-2), have been developed and widely used. Yet, it is not readily discriminated whether an observed effect of a CORM is caused by the release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 46 publications
3
50
0
Order By: Relevance
“…Lastly, with regard to the inhibition of anticoagulant activity by CORM-2, black mamba venom displayed no inhibition, whereas all three green mamba venoms had anticoagulant activity significantly and completely inhibited in PBS, but not in the presence of 5% human albumin. As with CORM-2-mediated inhibition of bee venom PLA 2 anticoagulant activity [18] and the modification of K + channels [20], albumin served as a "histidine sink" that reacts with a proposed Ru-based radical formed from CORM-2 while CO is being released. Our findings with CORM-2 are critical, as the mechanism by which the Ru-based radical effects its modification of proteins is most likely secondary to its binding to histidine residues or thiol groups, as reviewed in our recent work [18].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, with regard to the inhibition of anticoagulant activity by CORM-2, black mamba venom displayed no inhibition, whereas all three green mamba venoms had anticoagulant activity significantly and completely inhibited in PBS, but not in the presence of 5% human albumin. As with CORM-2-mediated inhibition of bee venom PLA 2 anticoagulant activity [18] and the modification of K + channels [20], albumin served as a "histidine sink" that reacts with a proposed Ru-based radical formed from CORM-2 while CO is being released. Our findings with CORM-2 are critical, as the mechanism by which the Ru-based radical effects its modification of proteins is most likely secondary to its binding to histidine residues or thiol groups, as reviewed in our recent work [18].…”
Section: Discussionmentioning
confidence: 99%
“…To substantiate this claim, the authors demonstrated that free histidine or albumin, which is resplendent with histidine residues, quenched the inhibition of potassium channels by CORM-2. Furthermore, using mass spectroscopy, the authors demonstrated histidine-Ru-based radical formation following exposure of free histidine with CORM-2 [14]. Lastly, using other various CORMs with other metal centers, the authors demonstrated no CO effects on the channel assessed [14].…”
Section: Introductionmentioning
confidence: 92%
“…However, cracks in the edifice of this paradigm began to appear in the year 2017 with the publication of a work that demonstrated CO-independent inhibition of K + channels with a putative Ru-based radical formed from CORM-2 during CO release and likely prior to formation of its iRM [14]. To substantiate this claim, the authors demonstrated that free histidine or albumin, which is resplendent with histidine residues, quenched the inhibition of potassium channels by CORM-2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, we and others already demonstrated the suitability of facial Mn(CO) 3 units for light-triggered administration of carbon monoxide [16] whereas in ruthenium-based and to al esser extentini ron-basedC ORMs the metal influence interferes with the CO-dependent modification of K + channels. [22] Solubility in aqueous media can be ensuredv ia formation of separated ions as realized for example, in non-toxic [{(OC) 3 Mn} 2 (m-SC 2 H 4 NH 3 ) 3 ]Br 2 (CORM-EDE1), [23] [(OC) 3 Mn{S(C 2 H 4 NH 2 ) 2 }]Br (CORM-EDE3), [18a] and [(OC) 3 Mn{(Pz Me2 ) 2 CHCH 2 OH)]Br (CORM-ONN1). [24] Reduction of the hydrophilicity already showeda nu nspecific uptake by living cells as demonstrated for [(OC) 3 Mn{S(C 2 H 4 NHCH 2 ) 2 }]Br (CORM-EDE4).…”
Section: Introductionmentioning
confidence: 99%